The impact of job demands-resources and personal resources on employees’ job performance in telecommunication engineering sector - Mohamud Shire, Abdirahman (2021)
Recently, research on job performance of employees of Telecommunication sector in Africa has received considerable attention, both in theory and practice. The job demands in Telecommunication sector has been reported to cause turnover intentions in employees, eventually leading to a decrease in job performance. The importance of this context is that, there is a growing interest in identifying ways to improve employees job performance. Therefore, this study aimed to examine the role of job demands-resources and personal resources on job performance of the employees of Somaliland Telecommunication companies. Specifically, the study aimed to identify the job performance level of employees in Somaliland telecommunication technology sector; to examine the influence of job demands-resources and personal resources on affective commitment, turnover intentions and work engagement of employees in Somaliland telecommunication technology sector; to examine the influence of affective commitment, turnover intentions and work engagement on job performance of employees in Somaliland telecommunication technology sector; to determine the mediating roles of affective commitment, turnover intentions and work engagement on the relationship between job demands-resources and personal resources with job performance of employees in Somaliland telecommunication technology sector. Data were collected from employees (N = 210) in Somaliland Telecommunication sector. This study is quantitative and it employs partial least squares structural equation modeling (PLS-SEM) to validate the research model to test the relationships being hypothesized. The study found the level of employees’ job performance to be moderate and a direct significant relationships among the tested variables. In addition, the multiple mediators of the study such as affective commitment, work engagement and turnover intentions are found to have partial mediating effect between JD-R model and job performance. Finally, the discussion of the findings, implications of the study, recommendations of the future work and conclusions were also discussed.